Nurses’ Burnout Level and Clinical Competence in Emergency Department: A Scoping Review - Nur 'Aini; Titin Andri Wihastuti; Tita Hariyanti; Juwitasari Juwitasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The condition of nurse fatigue includes emotional exhaustion, lack of respect for others, and decreased self-achievement (Burnout) results in the disruption of routine services in the Emergency Room. Routine services in the Emergency Room such as CPR procedures that require special nurse competence with zero tolerance will result in suboptimal results and delays in service. This literature study aimed to determine the relationship between nurse fatigue and nurse competence in the Emergency Room. The method used in writing this Scooping Review is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Searching for literature or references focuses on 2018 – 2022 and Original Research. The databases used in the search for references or literature are Pubmed, Proquest, Science Direct, and Google Scholar. The data was analyzed using the Joanna Briggs Institute (JBI) for cross-sectional, quantitative and prospective/cohort study. The results from 10 articles show a relationship between the nurses’ burnout level and clinical competence in the Emergency Department. A better arrangement of emergency units work patterns, such as proportional remuneration, regular supervision, rewards mechanism, safe operating conditions, cooperative team, balance nature of work, regular work promotion, and effective communication, could reduce the burnout level of the emergency nurse. Abstrak: Kondisi kelelahan perawat yang meliputi kelelahan emosional, kurang menghargai orang lain, dan penurunan prestasi diri (Burnout) mengakibatkan terganggunya pelayanan rutin di IGD. Pelayanan rutin di IGD seperti prosedur CPR yang membutuhkan kompetensi perawat khusus dengan zero tolerance akan mengakibatkan hasil yang kurang optimal dan keterlambatan pelayanan. Tujuan dari studi literatur ini adalah untuk mengetahui hubungan kelelahan perawat dengan kompetensi perawat di Instalasi Gawat Darurat. Metode yang digunakan dalam penulisan Scooping Review ini adalah PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses). Proses pencarian literature atau referensi berfokus pada tahun 2018 – 2022 serta Original Research. Basis data yang digunakan dalam pencarian referensi atau literatur adalah Pubmed, Proquest, Science Direct, dan Google Scholar. Data dianalisis menggunakan Joanna Briggs Institute (JBI) untuk studi cross sectional, kuantitatif dan prospektif/kohort. Hasil yang diperoleh dari 10 artikel adalah ada hubungan antara tingkat burnout perawat dengan kompetensi klinis di Instalasi Gawat Darurat. Penataan pola kerja unit gawat darurat yang lebih baik, seperti remunerasi yang proporsional, pengawasan teratur, mekanisme penghargaan, kondisi operasi yang aman, tim kooperatif, sifat keseimbangan kerja, promosi kerja reguler, komunikasi yang efektif, dapat mengurangi tingkat kejenuhan perawat gawat darurat.